Water and Sustainability - Thanjavur Chandrasekaran, Prathna (IntechOpen, 2019)
Floods and droughts brought about by the vagaries of nature cause extensive damage to the livelihoods of people as well as the environment. Knowledge of the need to adopt sustainable practices toward water use, reuse, and management is critical and the scope of this book deals precisely with sustainable practices in water management. The purpose of this book is to provide the reader with abundant and relevant information on all aspects related to water sustainability: water reuse, dynamics of transboundary waterways, economic tools to analyze sustainability, water-energy-food nexus, computer simulation models to study watershed models, and so forth. Although this book may not provide readers with comprehensive information on all aspects related to water sustainability, it will provide constructive data and content on the current trends and advancements in sustainable practices related to water. The book is intended to further motivate readers and scientists alike to look further and make concerted efforts toward promoting better and effective water management.